(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article describes the «color revolutions» as a political phenomenon, as a new type of political technologies and an aspect of their visualization. The experience of holding the «color revolutions» showed that the symbolism has become an important part of their organization. The symbolism of «color revolutions» have a special role in their influence on the electorate. In this case, the party symbolism are a powerful mobilizing and manipulating factor. Analyzed the symbolism of the «Orange Revolution» as a shining example of successful use of the symbol in the electoral process. It is shown how you can control the attitude of voters to a political party or a political leader by selecting a particular color, and how the creation of the necessary color environment can cause the desired emotions in the population. Key words: «color revolution», symbol, color, party symbolism.